Evaluasi Penggunaan Obat pada Pasien Dispepsia di Rumah Sakit Samarinda Medika Citra Tahun 2021: Evaluation of Medication Use in Patients with Dyspepsia at Samarinda Medika Citra Hospital in 2021 - Novia Syafitri; Adam M. Ramadhan; Muhammad Faisal (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Dyspepsia is defined as chronic or recurrent pain or discomfort centered in the upper abdomen that may originate from a variety causes. The right administration of drugs is a major concern when administrating drugs to dyspepsia patients to achieve the goal of drugs therapy itself. The aim of this study was to determine the characteristics of patients, the description of drug therapy and accuracy of medication use at Samarinda Medika Citra Hospital in January - August 2021. This study uses a non-experimental research design, data retrieval is done retrospectively and the analytical method is descriptive. The research instruments using 70 patient medical record data inclusions. The result revealed that the most characteristic data of dyspeptic patients was female by 55,71% (39 people), adult age group 26-45 years old by 42,86% (30 people), senior high school by 52,86% (37 people), other profession by 84,28% (59 people), patient with comorbidity by 71,43% (50 people). The most frequently prescribed anti-ulcer drugs for dyspepsia patients is combination of H2RA, Antiemetic and Cytoprotective approximately by 42,85% (30 people). The result showed that the right drugs by 100% (193 drugs), the right indications by 100% (193 drugs), and the right dosage by 96,37% (186 drugs).